2000
DOI: 10.1128/aem.66.8.3187-3193.2000
|View full text |Cite
|
Sign up to set email alerts
|

Common Degradative Pathways of Morpholine, Thiomorpholine, and Piperidine by Mycobacterium aurum MO1: Evidence from 1 H-Nuclear Magnetic Resonance and Ionspray Mass Spectrometry Performed Directly on the Incubation Medium

Abstract: In order to see if the biodegradative pathways for morpholine and thiomorpholine during degradation by Mycobacterium aurum MO1 could be generalized to other heterocyclic compounds, the degradation of piperidine by this strain was investigated by performing 1 H-nuclear magnetic resonance directly with the incubation medium. Ionspray mass spectrometry, performed without purification of the samples, was also used to confirm the structure of some metabolites during morpholine and thiomorpholine degradation. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…The detection of intermediates during morpholine degradation in Mycobacterium aurum MO1 and in an environmental Mycobacterium strain strongly indicates that the initial ring cleavage occurs at the C-N bond (Combourieu et al, 1998b(Combourieu et al, , 2000 , 1998). Studies have suggested that a cytochrome P450 catalyses the hydroxylation of the carbon atom of this bond (Combourieu et al, 1998a;Poupin et al, 1998Poupin et al, , 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of intermediates during morpholine degradation in Mycobacterium aurum MO1 and in an environmental Mycobacterium strain strongly indicates that the initial ring cleavage occurs at the C-N bond (Combourieu et al, 1998b(Combourieu et al, , 2000 , 1998). Studies have suggested that a cytochrome P450 catalyses the hydroxylation of the carbon atom of this bond (Combourieu et al, 1998a;Poupin et al, 1998Poupin et al, , 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation pathways of morpholine, thiomorpholine, and piperidine by Mycobacterium aurum MO1 and Mycobacterium sp. RP1 have been elucidated by in situ 1 H 1D NMR [50,51,57]. A pathway for the degradation of benzo[a]anthracene by Mycobacterium vanbaalenii PYR-1 in liquid culture has been proposed using 1 H NMR and HPLC analysis [58].…”
Section: Nmr Spectroscopy and Metabolite Profiling During Bioremediationmentioning
confidence: 99%
“…Microbial degradation by Gram-positive bacteria of heterocyclic secondary amines, including piperidine, has been reported mostly for members of the genus Mycobacterium, with very few reports for non-Mycobacterium species (Combourieu et al, 2000;Kim et al, 2006;Knapp et al, 1996;Poupin et al, 1999a, b;Trigui et al, 2003). The degradation pathways for compounds of all reported strains are proposed to be initiated by hydroxylation on a C atom adjacent to the amine group by cytochrome P450 monooxygenases, thereby forming unstable compounds A novel piperidine degradation mechanism in a newly isolated piperidine degrader Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%